RGEC INFLUENCE ON COMPANY VALUE (CASE STUDY ON ISLAMIC BANKING COMPANIES IN INDONESIA 2015-2019) (International Conference on Social and Islamic Studies, 2021)
The company's value is an assessment of investors, customers, and stakeholders on the company's condition that can be seen based on the market price value of the company's stock. This research aims to find out the influence of Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital (RGEC) on corporate value (Earning Per Share). This study uses regression analysis techniques panel data from the annual report of 12 Indonesian Islamic banks in the period 2015-2019. The data used in this study used quantitative data obtained from the Indonesia Stock Exchange (IDX) website and each Islamic bank website. The results of this study can be concluded that risk profiles have apositive and significant effect on the company's value. At the same time, good corporate governance (GCG), earnings, and capital are known to have a negative and in significant effect on the company's value. Advice for further research is to use variables other than NPF, the proportion of board of commissioners, ROE, or CAR so that the study results are different and add research time. The conclusion of this study is that the RGEC method in addition to being used for bank health assessment can also be used to assess companies through all four ratios.